Replacement Value of Maize with Sweet Potato (Ipomoea batata) Root Meal on Growth Performance and Haematogical Characteristics of Broiler Starter Birds - P. C. Jiwuba; E. Dauda; L. C. Ezenwaka; C. J. Eluagu (Archives of Current Research International, 2016)
A 28-day experiment was conducted to determine the effects of graded levels of sweet potato (Ipomoea batata) root meal (SPRM) on growth performance and haematological parameters of broiler starter birds. 240 day old unsexed Anak broiler chicks were used for this experiment. The birds were randomly divided into 4 groups with three replicates of twenty birds per replicate. Four dietary treatments designated as T1, T2, T3 and T4 were formulated to contain 0%, 5%, 10% and 15% levels of SPRM. The four groups were assigned the four experimental diets in a Completely Randomized Design. Feed and water were supplied ad libitum. Blood samples (4 ml) were drawn from the animals on the last day of the study through the wing vein and analysed for haematological indices. Results showed that treatment diet had significant (P<0.05) effect in all the growth and intake parameters evaluated. The average daily weight gain was highest (28.56 g) (P<0.05) for birds fed T2 diet and lowest (24.95 g) for T4 birds. The average daily feed intake was highest at T4 (62.62 g) and lowest (52.32) for T1. Feed conversion ratio was however relatively best for the birds fed T2 diet (1.90). Results also showed that mean cell volume (MCV), mean corpuscular haemoglobin (MCH) and white blood cell (WBC) counts differed (p<0.05) significantly among the groups. MCV and MCH was improved (p<0.05) by SPRT at 5% inclusion level. WBC count of birds in T1 was significantly (P<0.05) higher and better than the treatment groups. These results showed that inclusion of SPRM at 5% was best and supported weight gain, feed utilization and have no possibility of predisposing infections to broiler starters, nor interfere with haemapoetic process and therefore recommended for optimum broiler starter production.